Pengaruh Kedisiplinan dan Minat Baca Terhadap Prestasi Belajar IPA Siswa Kelas V SD Muhammadiyah 2 Kauman Surakarta Tahun 2015/2016 - Rohman, Anton Abdur (2016)
This study aims to determine: (1) Effect of discipline in the learning of the learning achievement of fifth grade science students of SD Muhammadiyah 2 kauman Surakarta (2) Effect of interest in reading the learning achievement of fifth grade science students of SD Muhammadiyah 2 Kauman Surakarta (3) Effect of discipline in learning and interest in reading the learning achievement of fifth grade science students of SD Muhammadiyah 2 Surakarta Kauman. This type of research is quantitative research. Subjects in this study are students of class V SD Kauman Muhammadiyah 2 Surakarta in 2015/2016. The data collection technique used was a questionnaire, documentation. Mechanical testing instruments used are validity and reliability testing. Techniques used prerequisite test is the test of normality and linearity test. Data analysis technique used is multiple regression analysis, t-test, f, coefficient of determination and looking for the contribution given. The first hypothesis of the calculation results obtained t> t table (2.227> 2.052) and sig <0.05 (0.034 <0.05). From the calculation of the second hypothesis is obtained t> t table (2.275> 2.052) and sig <0.05 (0.031 <0.05). The third hypothesis of the calculation results obtained F> F table (38.079> 3.32) and sig <0.05 (0.000 <0.05). So that the conclusions of this study are (1) discipline in the learning effect on learning achievement of fifth grade science students of SD Muhammadiyah 2 kauman Surakarta (2) interest in reading affect the learning achievement of fifth grade science students of SD Muhammadiyah 2 Kauman Surakarta (3) discipline in learning and interest read affect the learning achievement of fifth grade science students of SD Muhammadiyah 2 Surakarta Kauman.